Aquatic photolysis of ketoprofen generates products with photosensitizing activity and toxicity. (15th February 2022) - Wang, Lixiao; Zheng, Yajie; Zhou, Yiran; Lu, Junhe; Chovelon, Jean-Marc; Ji, Yuefei
Highlights: Photolysis of KTF produced photoproducts EtOH-BP, EtOOH-BP, AcBP, and EtBP. LFP confirmed the formation of triplet excited states of AcBP and EtBP. EtBP is photolabile while AcBP is relatively photostable. Both EtBP and AcBP have strong photosensitizing activity. KTF photoproducts have increased ecotoxicity to aquatic organisms. Abstract: Ketoprofen (KTF) is a nonsteroidal anti-inflammatory drug frequently detected in natural and engineering waters. Because KTF is particularly photolabile (half-life ∼4 min), knowledge of the fate and ecological risks of KTF photoproducts in the aquatic environment is especially essential. Herein, we systematically investigated the photophysics, photochemistry, and photosensitization of KTF photoproducts in aqueous solution under 365 nm irradiation (UV365 ). Results show that KTF photolyzed rapidly and formed 3-ethyl- α -hydroxylbenzophenone (EtOH-BP), 3-ethyl- α -hydroperoxylbenzophenone (EtOOH-BP), 3-acetylbenzophenone (AcBP), and 3-ethylbenzophenone (EtBP), as identified by liquid chromatography-tandem mass spectrometry (LC-MS/MS) and high-resolution mass spectrometry (HRMS). The presence of O2 significantly affected the evolution of photoproducts during KTF photolysis. The photophysical properties of EtBP and AcBP were characterized by spectroscopic approaches. In particular, transient absorption spectra obtained by nanosecond laser flash photolysis (LFP) indicated that EtBP and AcBP were excited to triplet states with lifetimes of 28 and 2.4 µs, respectively. EtBP underwent further photodegradation, giving rise to EtOH-BP, EtOOH-BP, and AcBP upon UV365 irradiation. The reaction is proposed to proceed through an excimer precursor ( 3 [EtBP···EtBP]*) followed by intramolecular H-abstraction. In contrast, AcBP was relatively photostable, particularly under aerated condition. Both EtBP and AcBP have strong photosensitizing activity, as evidenced by the triplet probe 4-( N, N -dimethylamino)benzonitrile (DMABN). ECOSAR program suggested that the photoproducts are more ecotoxic and bioaccumulative than the parent KTF. Results of this study underscore the need to scrutinize the formation and fate of KTF photoproducts in sunlit surface waters. Graphical Abstract: Image, graphical abstract